Analisis Korelasi Stigmatisasi dengan Kecemasan pada Penderita Tuberkulosis yang Sedang Menjalani Pengobatan - Efendi, Sudirman; Wahyuni, Sri; Syarif, Iqwan; Nusi, Winda Rahmatia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the relationship between stigmatization and the level of anxiety felt by tuberculosis patients undergoing treatment in the Kassi-Kassi Community Health Center working area in Makassar City. The study used a quantitative correlation research method with a Cross Sectional Study approach and used the Spearman test. The results of this study showed p Value = 0.000 (p <0.05) which means Ha is accepted or in other words there is a significant relationship between stigmatization and anxiety felt by tuberculosis patients. So it can be concluded that the stigma obtained from family or society causes tuberculosis sufferers to experience anxiety and will have an impact on the healing process during treatment. Keywords: Anxiety, Stigma, Tuberculosis